Physical exercise interventions for perinatal depression symptoms in women: A systematic review and meta-analysis - Liu, Xueyan; Wang, Guangpeng; Cao, Yingjuan (Frontiers in Psychology, 2022)
Background: The previous meta-analysis indicated that physical exercise could play a crucially therapeutic role in reducing perinatal depression symptoms in women. However, the efficacy varies across different exercise types, forms, intensities, and duration. Aim: The purpose of this study was to review and evaluate the effects of different types, forms, intensities, and duration of exercise for improving perinatal depressive symptoms. Design: A systematic review and meta-analysis. Methods: Randomized controlled trials until December 2021 were searched from seven databases, including PubMed, EMBASE, Medline, CINAHL, Web of Science, Cochrane Library, and PsycINFO. The risk of bias in eligible trials was evaluated using the Cochrane Risk of Bias tool. When high heterogeneity was tested, we used random-effects models. A funnel plot was used to assess the publication bias. This review was performed under the PRISMA guidelines, Consensus on Exercise Reporting (CERT) checklist and Cochrane Handbook. The certainty of the body of evidence was assessed using the GRADE method. Results: Of 1573 records, 20 trials were identified in this study. The results of this review revealed that women with perinatal depression symptoms gained benefits from physical exercise (OR = 0.62, 95% CI [0.45, 0.86], P=0.004; MD = -0.57, 95% CI [-0.83, -0.30], P<0.0001). Type of walking (SMD = -1.06, 95% CI [-1.92, -0.19], P<0.00001), form of “Individual + group-based ”exercise (SMD = -0.91, 95% CI [-0.80, -0.03], P = 0.04), intensity of ≥150 mins per week (SMD = -0.84, 95% CI [-1.53, -0.15], P=0.02) and ≥12 weeks duration (SMD = -0.53, 95% CI [-0.75, -0.31], P < 0.00001) seemed to generate more prominent improvement on perinatal depression symptoms. Conclusions: Physical exercise showed a significant effect on reducing perinatal depressive symptoms. This meta-analysis provides an important update on exercise's efficacy in treating perinatal depression. Further higher quality and large-scale trials are needed to substantiate our findings.